The Relationship Between Self-Training on (Ruang GTK) and Teacher Creativity in Learning with the Performance of SMP Teachers in Walantaka District, Banten Province - Aprian Darmayanti; Aan Asphianto; Lukman Nulhakim (International Journal of Community Engagement Payungi, 2025)
Education plays a pivotal role in shaping competitive and high-quality human resources. In this process, teachers serve as key agents of change whose performance significantly impacts educational outcomes. However, the performance of junior high school teachers in Walantaka District, Serang City remains suboptimal, marked by inadequate lesson planning, limited technology integration, and low creativity in instructional strategies. This study aims to examine the relationship between self-directed training on the Ruang GTK platform and teacher creativity in learning with overall teacher performance. Employing a quantitative correlational method, data were collected from 54 teachers selected using purposive sampling from three public junior high schools. The study used questionnaires and analysed the data with linear regression and correlation analysis via SPSS. The results revealed a strong positive correlation between self-training and teacher performance (r = 0.623, p < 0.05), as well as between teacher creativity and performance (r = 0.580, p < 0.05). Additionally, the joint influence of both variables showed a significant effect on teacher performance (R = 0.703; R² = 0.494). The novelty of this study lies in integrating a digital self-training platform (Ruang GTK) and pedagogical creativity as joint predictors of teacher performance an approach that has rarely been quantitatively assessed in the Indonesian educational context. The original contribution of this study is the empirical evidence supporting Ruang GTK as a scalable solution to teacher development, especially where conventional training access is limited. In conclusion, optimizing self-training and fostering creativity can serve as a strategic framework to enhance teacher competence and, ultimately, improve the quality of learning and education.